Package and practices of temperate fodder crops in Jammu and Kashmir valley of the north-western Himalayas - Verma, Dilip Kumar; Ahmad, Suheel; Meena, Kanhaiya Lal; Meena, Gopal Lal (Indian Farming, 2019)
Green forages when dried to about 80-85% dry matter, containing most of its nutrients including cardene, is called hay. The moisture concentration in hay must be less than 15% at storage time. However, crops with thin stems and many leaves are better suited for hay making as they dry faster than those having thick and pithy stems and small leaves. Natural grasses oats, lucerne, are highly suitable for hay making which is used for lean period.